A study of collocation errors among Chinese learners of English (with reference to Chinese college students of Tongji university in China) / Ye Hong - Ye, Hong (2014)

(untitled)
This study focuses on collocation errors among Chinese learners of English. The main purposes are: 1) to describe and contrast the collocations of Chinese (Mandarin) and English; 2) to explain the occurrence of the major types of errors of English collocations committed by the Chinese learners of English; 3) to identify the areas of difficulty including the MT interference and hierarchy of difficulty encountered by the Chinese learners in the use of English collocations using CA and EA. To achieve these goals, both English and Chinese collocations are described and compared, which has been received little attention in the past. The data was collected from one writing task administered during classroom hours. The learner corpus consisted of 117 pieces of written texts. In the data analysis, received categories about linguistic errors were critically scrutinized. Wordsmith Tool with concordance lines of BNC and LC was employed to highlight selected KWIC. Oxford Advanced Learner Dictionary was also used to identify and analyze errors. SPSS and MicroFinder were employed to count the numbers and percentages of errors in the EA. CA involves two methods - theoretical CA and applied CA, the latter of which is also Error Analysis (EA). The former is aimed at predicting potential learning difficulties by analyzing the differences between the structures of MT and TL. The latter is aimed at identifying and explaining actual errors committed by the students. In fact, both approaches are useful in the explanation of errors in a TL. This study gave a detailed description of the procedure of EA in concurrence with the CA method. This study identified seven categories of English collocation errors. They were errors on noun + noun / prepositional phrase collocation, noun + verb / phrasal verb iii collocation, verb / phrasal verb + noun collocation, adjective + noun collocation, verb + adverb collocation, adverb + adjective + noun collocation, and a / numeral + quantifying noun + of + head noun collocation. Errors on English subject-predicate structures were found to be the most common among all subcategories of English collocations among Chinese learners of English, followed by English verb + noun collocation errors, and adverb + verb and adverb + adjective + noun collocation errors were the least common. English attributive modifier + head noun collocations are less common than verb + noun collocation errors. Intralingual source of errors found in the context such as ignorance of restrictive collocation rules of English was found to be most responsible for English collocation errors committed by Chinese learners of English. From lexical and grammatical levels of collocations, violation of English lexical collocations is found more than that of grammatical collocations. They are grammatically and semantically plausible but inappropriate use in the context. In terms of syntax, English collocation errors were traced back to interference from the MT. Chinese compounds, Chinese non-phrasal verbs and non-inflectional morphology in part-of-speech were structurally different from English and thus interfered with the learning of English collocations among Chinese learners of English. Areas of difficulty in the learning of English collocations and the hierarchy of difficulty identified from CA were found to keep agreement with those found from EA. Hence, this verifies that Contrastive Analysis (CA) is a useful tool to predict potential problems facing learners. Intralingual errors and errors due to circumlocution (using more words than necessary) identified from EA indicate that EA is a complement to CA in identifying all possible learner errors. Therefore, blending of CA into EA to construct an iv integrated theory and approach is significant in the identification, explanation and identification of TL errors. Pedagogically, the finding implies that CA-based methodology will enable students to locate and focus on the difficulties in learning English vocabulary to enhance teaching effectiveness. EA can be helpful in identifying all possible errors and thus overcoming them. Learning strategies such as collocation strategy is important for learners in the learning of English vocabulary.